ANALISIS ASUHAN KEPERAWATAN PADA PASIEN PASCA STROKE DENGAN PENERAPAN INTERVENSI RANGE OF MOTION (ROM) PASIF UNTUK MENINGKATKAN KEKUATAN OTOT. - Bunga Indah Sari (2023)
Stroke is defined as a clinical condition caused by reduced tissue vascularization in the brain, resulting in disturbances in several functions such as sensory function, noble function, coordination, autonomic, motor function, and cranial nerves. One of the symptoms experienced by patients with stroke is weakness in the muscles of the limbs, atrophy and postural disturbances. One form of initial rehabilitation for stroke patients is to provide mobilization in the form of ROM (Range Of Motion) both passive and active. This exercise is performed to improve and maintain the ability to move joints normally, increase muscle mass and tone. Implementation of passive ROM exercise interventions in patients for 3 meetings for 3 days. The results of implementing passive ROM exercises are where there is an increase in muscle strength, joint stiffness gradually begins to disappear and muscles become more relaxed than before passive ROM was done. From these results it can be concluded that passive ROM exercises are effective given to post-stroke patients to increase muscle strength. Nurses are expected to implement passive ROM exercises as the main non-pharmacological therapy in patients with muscle weakness.